Analisis Kelayakan Usaha Produk Kacang PILBAR Di Desa Pilohayanga Barat - Liputo, Siti Aisa; Bait, Yoyanda; Antuli, Zainuddin (Jurnal Pengabdian Masyarakat Teknologi Pertanian, 2022)
This article contains about business feasibility analysis of PILBAR products to three processed peanut products in West Pilohayanga Village, Telaga District, Gorontalo District. The purpose of this article is to explain the feasibility analysis on three processed peanut products in West Pilohayang Village, Telaga District, Gorontalo District, on three processed peanut products which are used to be profitable and feasible to be developed / continued or even vice versa. This research is conducted by direct interview method and questionnaire also with business feasibility analysis using Break Event Point (BEP), Revenue Cost Rati (R / C ratio) and Efficiency Analysis of Capital (ROI). From this article, it can be concluded that business feasibility analysis of PILBAR products on three processed products made by the community in West Pilohayang Village Telaga District can be developed because the products sold are proved to sell well in all circles of society, whether done in the form of promotion through social media such as facebook and others, also through the media website. Thus, with the number of processed peanut products sold then based on the analysis of business feasibility analysis of the three processed peanut products can be developed / continued business.